2018
DOI: 10.15252/emmm.201708699
|View full text |Cite
|
Sign up to set email alerts
|

Cancer cell adaptation to hypoxia involves a HIF‐GPRC5A‐YAP axis

Abstract: Hypoxia is a hallmark of solid tumours and a key physiological feature distinguishing cancer from normal tissue. However, a major challenge remains in identifying tractable molecular targets that hypoxic cancer cells depend on for survival. Here, we used SILAC‐based proteomics to identify the orphan G protein‐coupled receptor GPRC5A as a novel hypoxia‐induced protein that functions to protect cancer cells from apoptosis during oxygen deprivation. Using genetic approaches in vitro and in vivo, we reveal HIFs as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
61
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(67 citation statements)
references
References 52 publications
2
61
2
Order By: Relevance
“…GPRC5A is highly expressed in colorectal cancer (CRC), and elevated GPRC5A expression is significantly associated with inferior prognosis [ 87 , 88 ]. In addition, liquid chromatography analysis demonstrates that GPRC5A expression is lower in polyps than in metastatic and non-metastatic CRC samples, suggesting that GPRC5A may serve as a biomarker to differentiate CRC from normal tissues [ 89 ].…”
Section: Gprc5a and Its Role In Human Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…GPRC5A is highly expressed in colorectal cancer (CRC), and elevated GPRC5A expression is significantly associated with inferior prognosis [ 87 , 88 ]. In addition, liquid chromatography analysis demonstrates that GPRC5A expression is lower in polyps than in metastatic and non-metastatic CRC samples, suggesting that GPRC5A may serve as a biomarker to differentiate CRC from normal tissues [ 89 ].…”
Section: Gprc5a and Its Role In Human Cancermentioning
confidence: 99%
“…What is more, GPRC5A deficiency reduces cell proliferation and promotes cell apoptosis in vitro and inhibits tumorigenesis of a colitis-associated cancer model in vivo . Furthermore, GPRC5A can be induced by hypoxia, regulates the NF- κ B-mediated expression of Vanin-1 (a key enzyme of cysteamine generation), and influences the reactive oxygen levels contributing to tumor progression [ 88 , 90 ].…”
Section: Gprc5a and Its Role In Human Cancermentioning
confidence: 99%
“…[ 274 ] Hypoxia was reported to repress LATS1/2 gene expression to promote YAP activation during endometriosis, [ 275 ] while another group found that hypoxia induced expression of an orphan GPCR, the GPCR5A gene, to activate YAP in colonic epithelial cells. [ 276 ] YAP was also reported to maintain HIF‐1alpha expression. [ 277 ] Others reported that Hypoxia promoted YAP nuclear localization via direct YAP‐HIF‐1alpha binding.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, GPRC5A has been identified as a novel hypoxia-induced protein that functions to protect cancer cells from apoptosis during oxygen deprivation and was found to be upregulated in colorectal cancers. Mechanistically, GPRC5A acts via the Hippo pathway effector YAP 48 . However, in non-small cell lung carcinoma (NSCLC), GPRC5A is expressed as much lower levels than in the corresponding noncancerous tissues and was associated to a worse prognosis 46 .…”
Section: Discussionmentioning
confidence: 99%